Experimental Study on the Dynamic Rock-Breaking Performance of Pulsed Abrasive Jet Drilling Method - Yukun Du; Xiaohong Chen; Bo Zhao; Zhiyuan Huang; Meilian Wu; Diangang Bai; Guoliang Hao; Qingshi Meng; Zhenhua Mei; Xiaocheng Chen (Shock and Vibration)
The efficient development of deep oil and gas reservoirs with abundant resources is conducive to meet the growing energy demand. However, it is very difficult to drill in the deep reservoirs such as tight sand gas and shale gas because of their high strength, low porosity, and low permeability. In this study, it is pointed out that developing high-efficiency drilling methods based on new combined water jets is a good approach to promote the rate of penetration (ROP) in such tight deep reservoirs. A pulsed abrasive water jet drilling tool is designed, and its dynamic work principle is analyzed. The hydraulic structure is optimized; meanwhile, the rock-breaking experiments of this structure are carried out. The results show that the rock-breaking performance of the pulsed water jet is much better than that of the continuous water jet. It is also found that the rock-breaking performance of the pulsed abrasive water jet is much better than that of the premixed abrasive water jet. In addition, the best rock-breaking standoff distance, abrasive concentration, and particle size are detected.